Role of Interventional Radiology in the Management of Pancreatic Trauma - Celii, Francis G.; Zvavanjanja, Rodrick C. (Digestive Disease Interventions, 2025)
Pancreatic trauma is uncommon, occurring in less than 2% of blunt trauma cases. Typically, it occurs in connection with multiple injuries after motor vehicle accidents in adults and bicycle handlebar injuries in children. Prompt identification of such injuries is important given the high morbidity and mortality with delayed diagnosis, incorrect classification, or delays in treatment. As key members of the trauma team, interventional radiologists may be involved in pancreatic trauma care as part of other organ injuries (spleen, liver, renal, etc.) or as isolated pancreatic injury. Minimally invasive image-guided procedures play a critical role in the management of pancreatic trauma patients. Understanding the patterns of pancreatic injury and expected complications is critical in delivering appropriate treatment for these patients. Through case presentations, this article will review the role of interventional radiology in the management of pancreatic injuries and provide state-of-the-art image-guided management options for pancreatic injuries and secondary trauma-related pancreatic complications.
Keywords: pancreatic trauma; pancreatic embolization; pancreatic hemorrhage